The internal customer satisfactions towards USIM's Quality Management Unit Services / Haqimi Malek - Malek, Haqimi (Faculty of Business and Management, 2009)
There are a lot of previous researches focusing to the customer satisfaction topic. In this research, the main objective is to determine the level of customer satisfaction; however, this research will be focusing customer satisfaction in internal customer perspectives. Using the three of services elements which is communication, interpersonal skills, and responsiveness, this research seek the internal customer satisfaction towards services that been provided by USIM's Quality Management Unit. This research were using questionnaire in order to collect the data and the questionnaire will be distributed to four main departments in USIM namely Department of Student Affairs (HEP), Department of Treasurer, Department of Library, and Department of Registrar. The study sample consisted of 135 respondents or employees from those four departments. The questionnaires of this research are analyzed using the SPSS technique. All the data collected from the respondents are keyed in and will be processed by SPSS. The frequency, mean, one-way ANOVA, and correlation conducted using the SPSS in order to analyze all the data needed. As a result, this research found that level of customer satisfaction toward UPK services is good and customers are satisfied with UPK responsiveness followed by communication and interpersonal skills. There are also significant relationship between all service factors such as communication, interpersonal skills, and responsiveness with customer satisfaction. In addition, responsiveness is the most influence factor that influenced customer satisfaction followed by interpersonal skills and communication. From the result that has been analyze, researcher suggest that in order to improve UPK customer satisfaction level, they need to concentrate more on their responsiveness since it is the most influence factor to customer satisfaction. Researcher also recommends that UPK also need to improve their interpersonal skills and communication even though both of the factor give less influence to their customer satisfaction.